The “Who” System of the Human Brain: A System for Social Cognition About the Self and Others - Brown, Steven (Frontiers in Human Neuroscience, 2020)
Neuroscientists are fond of talking about brain systems for the processing of “what” and “where” information about objects and their locations. What is critically missing is the concept of a “who” system dedicated to the neural processing of information about social agents—both the self and others—and their interactions. I propose here the characterization of such a system, one that functions not only in perception but in production as well, such as when recounting stories about oneself and others. The most human-specific features of the “who” system are two complementary systems that I refer to as the other-as-self mechanism and the self-as-other mechanism. The major function of the other-as-self mechanism is to perceive other people egocentrically as proxies of the self, as occurs through the processes of mentalizing and empathizing in both everyday life and in the experience of the theatrical and literary arts. The major function of the self-as-other mechanism is to overtly depict other people during acts of communication through vocal and gestural processes of mimicry, such as occurs during quotation in conversation and through acting in the theatrical arts. Overall, the “who” system of the human brain mediates both perceptual and behavioral aspects of social cognition, and establishes the existential distinction between self and other in human cognition. I present neural models for the instantiation of the “who” system in the human brain and conclude with a discussion of how narrative serves as a foundation for human cognition more generally, what I refer to as narrative-based cognition.